Le défi du pluralisme et la contestation juridique d'une formation obligatoire pour toutes et tous en Éthique et culture religieuse - Bégin, Luc (Zeitschrift für Religionskunde, 2016)
The Ethics and Religious Culture (ERC) syllabus applied in Quebec since 2008 represents the last phase in a slow process of deconfessionalisation of schools in the province. The response that this non-confessional curriculum brings to the challenge of the pluralism of Quebec society has given rise to some opposition, including two legal challenges. In both cases, the obligatory character of the syllabus was called into question. This article analyses these two legal challenges, situating the main arguments that were developed in relation to the objectives and structure of the ERC syllabus. The importance of maintaining the obligatory character of the syllabus- so as to respond adequately to the challenge of pluralism - and the question of infringement of the freedom of religion to which the judges at the various levels paid particular attention - are central to the analysis.